Preparation method of quaternized chitosan-succinic acid-based hollow salt and application of quaternized chitosan-succinic acid-based hollow salt in air-dried duck meat
The preparation of quaternary ammonium chitosan-succinic acid hollow salt through specific mixing and ultrasonic spray drying addresses stability and uniformity issues, enhancing saltiness and sensory quality in air-dried duck meat, providing a healthier alternative to traditional salt reduction methods.
Patent Information
- Application Number
- CN202411707537.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-27
AI Technical Summary
Existing methods for reducing salt in food products, such as air-dried duck meat, face challenges with equipment compatibility, flavor changes, and safety issues, while hollow salt technology requires improvements in stability, uniformity, and salt-enhancing effectiveness.
A method involving the preparation of quaternary ammonium chitosan-succinic acid hollow salt by mixing quaternary ammonium chitosan, succinic acid, and NaCl, followed by ultrasonic treatment and spray drying, with specific conditions to enhance cross-linking and uniformity, resulting in a stable and effective salt-enhancing product.
The prepared hollow salt significantly increases saltiness with reduced quantities of NaCl, inhibits lipid oxidation, and improves sensory quality of air-dried duck meat, offering a healthier alternative with broader application potential in food processing.
Smart Images

Figure CN119184278A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of manufacturing functional food ingredients, in particular to a method for preparing quaternary ammonium chitosan-succinic acid hollow salt and application of the quaternary ammonium chitosan-succinic acid hollow salt in air-dried duck meat. Background Art
[0002] Sodium chloride (NaCl) is a commonly used additive in food processing. In the processing of air-dried meat products such as dry-cured ham and air-dried duck, a large amount of NaCl is needed to ensure the texture and color of the meat products and prevent corruption. Long-term intake of high-salt foods can cause the body to suffer from high blood pressure, blood vessel blockage, chronic kidney disease, osteoporosis and other diseases, increasing health risks. Therefore, it is urgent to develop ingredients that reduce salt and increase saltiness to replace NaCl for food processing, especially for the production of air-dried meat products. At present, common methods of reducing salt in food include vacuum curing, high-pressure curing, pulse curing, gamma irradiation, potassium salt, calcium salt substitution, plant salt substitution and other technologies. Vacuum curing and other methods are difficult to use in practice due to the matching problem between equipment and raw materials; potassium salt substitution has a metallic bitter taste, calcium salt substitution makes food astringent, and plant salt may affect color and flavor, and its composition is complex, and food safety is questionable. Therefore, it is urgent to develop a new processing method for reducing salt and increasing saltiness in food.
[0003] In view of the limitations of traditional salt reduction technology, hollow salt has attracted attention as an emerging technology. This technology mixes NaCl with polysaccharide shell materials and uses processes such as spray drying to prepare hollow salt particles. This hollow structure can encapsulate and control the release of salt by physical and chemical means to achieve the purpose of enhancing salty perception, reducing salt dosage, and improving food texture and flavor. The development of hollow salt caters to the demand for low-salt healthy food in the modern food industry while maintaining a good salty and flavor experience. The raw materials for preparing hollow salt are usually polysaccharides, such as chitosan, gum arabic, carrageenan, etc. The important mechanism of increasing the saltiness of hollow salt using polysaccharides as raw materials is its regulation of taste perception, which can be explained from three aspects. First, polysaccharides can increase the local concentration of salty substances through their colloidal effect, increase the stimulation of taste receptors, and thus enhance the perception of saltiness. Secondly, the viscosity and solubility of food will affect the diffusion and perception speed of salty substances in the mouth. By increasing the viscosity of food, polysaccharides can slowly release the salty taste in the mouth, prolonging the perception time of the salty taste. In addition, polysaccharides can act as a physical barrier to salty substances, allowing them to be slowly released during chewing, preventing the salty taste from dissipating quickly. Thirdly, some polysaccharides can directly interact with taste receptors, changing the taste receptors' sensitivity to Na. +The sensitivity of salty taste receptors. For example, the positive charge of chitosan can interact with the negative charge on the salty taste receptor, change its sensitivity to sodium ions, and thus enhance the perception of salty taste. The use of polysaccharides as raw materials to prepare hollow salts by spray drying has many practical advantages. For example, the hollow particles formed by spray drying can effectively encapsulate NaCl, protect it from environmental factors such as deliquescence or oxidation, and extend the shelf life of salt. Secondly, the hollow structure can adjust the release rate of saltiness, reduce the abruptness of saltiness, make it milder and more lasting, and is particularly suitable for foods that need to release saltiness slowly. In addition, spray drying is a common industrial production technology that is simple and easy to control, suitable for large-scale production, and polysaccharide-salt solution can be used to prepare hollow salt particles at one time by spray drying, and the process is efficient. As a natural biopolymer, polysaccharides have the advantages of being non-toxic, degradable, and edible. However, there are also some problems in the preparation of hollow salts. For example, the spray drying process is greatly affected by environmental conditions (such as temperature and humidity). Too high a temperature may cause polysaccharide degradation or structural changes in salts. Too low a temperature may affect the efficiency of spray drying and the quality stability of the product. There is also the problem of the uniformity of hollow salt: improper control during the spray drying process may lead to uneven distribution of polysaccharides and salt, and inconsistent saltiness of hollow salt particles, affecting the quality and consistency of the product. Therefore, it is particularly important to develop a hollow salt preparation process with high stability, significant salt-enhancing effect and uniform particles. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a quaternary ammonium chitosan-succinic acid hollow salt with high stability, significant salt-enhancing effect and uniform particles, and its application in air-dried duck meat, thereby inhibiting lipid oxidation of the air-dried duck meat and improving the sensory quality of the product.
[0005] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing a quaternary ammonium chitosan-succinic acid hollow salt, comprising the following steps: mixing quaternary ammonium chitosan, succinic acid, NaCl and deionized water in a mass ratio of 1:2.36:15:81.64, stirring and uniformly dissolving, treating under ultrasonic conditions of 100 to 500 W for 20 to 40 min, spray drying after the end of the ultrasonic treatment, and obtaining a quaternary ammonium chitosan-succinic acid hollow salt embedded with NaCl.
[0006] Preferably, during the spray drying process, the inlet air temperature of the spray dryer is set to 140° C., the fan frequency is set to 10 rpm, and the solution injection speed is set to 20 mL / min.
[0007] Preferably, the water bath temperature is set to 60° C. during ultrasonic treatment.
[0008] Preferably, the ultrasonic power is 400W or 500W.
[0009] The invention also provides application of the quaternary ammonium chitosan-succinic acid hollow salt obtained by the preparation method in air-dried duck meat.
[0010] Furthermore, the added mass percentage of hollow salt used for pickling duck meat is 6%, the air-drying time is 3 days, and the air-drying temperature is 16°C.
[0011] Compared with the prior art, the advantages of the present invention are: a method for preparing a quaternary ammonium chitosan-succinic acid hollow salt and its application in air-dried duck meat; the quaternary ammonium chitosan and succinic acid have a high degree of cross-linking, so that the shell layer of the hollow salt is more solid; ultrasonic treatment can make the shape of the hollow salt smoother and fuller, the breakage rate is reduced, the crystal structure is stable, and the particle size distribution of the hollow salt is more uniform and smaller, reaching less than 10 μm, which is conducive to increasing the embedding amount of NaCl in the hollow structure, so that the hollow salt Na + The maximum loading amount exceeded 300 mg / kg, and the dissolution temperature of the hollow salt after ultrasonic treatment increased, which improved its thermal stability and was conducive to its storage stability. The results of electronic tongue and sensory evaluation showed that ultrasonic 400W and 500W treatment can significantly increase the saltiness of the hollow salt, and the saltiness of pure NaCl can be achieved by using only 45.36-53.71% of the weight of pure NaCl. Further use of hollow salt to marinate duck meat inhibited lipid oxidation of air-dried duck meat, and the overall sensory score of air-dried duck meat was higher than that of marinating with NaCl alone, indicating that the hollow salt also has a sensory improvement effect in practical applications. The hollow salt prepared by this method can further expand its application range to the production of foods such as cheese and kimchi in the future, and has broad application prospects in the food processing industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 The figure shows the effects of different treatment methods on hollow salts, where A is the cross-linking degree of hollow salts, B is the NaCl embedding amount of hollow salts, C is the infrared spectrum of hollow salts, D is the X-ray diffraction spectrum of hollow salts, E is the differential scanning calorimetry (DSC) analysis result of hollow salts, and F is the experimental results of rheological properties of hollow salts; Qac: quaternized chitosan, WB: only water bath heating treatment without salt, WB-NaCl: only water bath heating treatment for embedding salts, US100W: ultrasonic 100W treatment for 30 min embedding salts, US200W: ultrasonic 200W treatment for 30 min embedding salts, US300W: ultrasonic 300W treatment for 30 min embedding salts, US400W: ultrasonic 400W treatment for 30 min embedding salts, US500W: ultrasonic 500W treatment for 30 min embedding salts; Figure 2The electronic tongue tests the taste of hollow salt obtained by different treatment methods and the actual human sensory evaluation results, where A is the saltiness intensity of the hollow salt solution, B is the taste richness of the hollow salt solution, C is the sourness intensity of the hollow salt solution, D is the umami intensity of the hollow salt solution, and E is the actual human sensory evaluation result of the hollow salt; Figure 3 is the particle size distribution of hollow salt spray-dried after different pretreatment methods, wherein A is the particle size of quaternized chitosan raw material, B is the particle size without salt after water bath heating treatment, C is the particle size containing salt after water bath heating treatment, D is the particle size of hollow salt spray-dried after ultrasonic 100W pretreatment, E is the particle size of hollow salt spray-dried after ultrasonic 200W pretreatment, F is the particle size of hollow salt spray-dried after ultrasonic 300W pretreatment, G is the particle size of hollow salt spray-dried after ultrasonic 400W pretreatment, and H is the particle size of hollow salt spray-dried after ultrasonic 500W pretreatment; Figure 4 The results of the microstructure observation of hollow salts obtained by different treatment methods, where A is the hollow salt obtained by water bath heating treatment, B is the particle size of the hollow salt spray-dried after ultrasonic 100W pretreatment, C is the particle size of the hollow salt spray-dried after ultrasonic 200W pretreatment, D is the particle size of the hollow salt spray-dried after ultrasonic 300W pretreatment, E is the particle size of the hollow salt spray-dried after ultrasonic 400W pretreatment, and F is the particle size of the hollow salt spray-dried after ultrasonic 500W pretreatment; Figure 5 These are the results of the effect of hollow salt pickling on air-dried duck meat obtained by different treatment methods, among which A is the effect of hollow salt on the pH of air-dried duck meat, B is the effect of hollow salt on TVB-N of air-dried duck meat, C is the effect of hollow salt on TBARS of air-dried duck meat, NaCl group is air-dried duck meat pickled with only 6% normal salt, 100W group is air-dried duck meat pickled with hollow salt after 100W ultrasonic-spray drying, 200W group is air-dried duck meat pickled with hollow salt after 200W ultrasonic-spray drying, 300W group is air-dried duck meat pickled with hollow salt after 300W ultrasonic-spray drying, 400W group is air-dried duck meat pickled with hollow salt after 400W ultrasonic-spray drying, and 500W group is air-dried duck meat pickled with hollow salt after 500W ultrasonic-spray drying. DETAILED DESCRIPTION
[0013] The present invention is further described in detail below with reference to the accompanying drawings.
[0014] Embodiment 1, a method for preparing quaternized chitosan-succinic acid hollow salt, comprising the following steps: 1 g of quaternary ammonium chitosan and 2.36 g of succinic acid were dissolved in 81.64 mL of ultrapure water and magnetically stirred for 30 min to fully dissolve the two. Then, 15 g of NaCl was added and stirred evenly. The mixture was placed in an ultrasonic processor with a water temperature of 60 °C and different ultrasonic powers of 100 W, 200 W, 300 W, 400 W, and 500 W were set for treatment for 30 min (). Then, the solution was placed in a spray dryer with the inlet temperature set at 140 °C, the fan frequency set at 10 rpm, and the solution injection rate set at 20 mL / min to obtain quaternary ammonium chitosan-succinic acid hollow salt encapsulating NaCl.
[0015] The hollow salt prepared by replacing the ultrasonic treatment time in the above production process with water bath heating is recorded as WB-NaCl. The hollow salt prepared by replacing the ultrasonic treatment time in the above production process with water bath heating and no NaCl is added is recorded as WB.
[0016] Example 2, hollow salt crosslinking degree and Na prepared in Example 1 + Content determination and sensory evaluation results.
[0017] Take 5 mL of 1wt% hollow salt solution, add 10 μL of 1wt% toluidine blue solution, mix well, and titrate the solution with 0.1 mol / L polyvinyl potassium sulfate (PVSK) to make the solution color change from blue to purple and not fade within 30 s. The calculation steps of cross-linking degree are divided into two steps: first, titrate the NH2 content in the solution, NH2 (%) = (C pvsk *ΔV*161.15*100) / (5*c)*100%, C pvsk is the concentration of PVSK reagent used, ΔV is the volume of PVSK reagent consumed, 161.15 is the average molecular weight of quaternized chitosan, and c is the concentration of hollow salt solution. Then the cross-linking degree Y (%) = 1-[NH2% (b) / NH2% (a)] * 100% is further calculated, where NH2% (a) is the NH2% content in the quaternized chitosan raw material, and NH2% (b) is the free NH2% content in the hollow salt after cross-linking.
[0018] Take 0.2 g of hollow salt powder and dissolve it in 5 mL of nitric acid solution and let it stand for 12 h. Then transfer the solution to the microwave digestion system and digest it for 20 min. Then dilute the digestion solution to 100 mL with deionized water and use atomic flame absorption spectrometer to measure the Na + Ion content.
[0019] The hollow salt powder was dissolved in deionized water to prepare a solution with a mass concentration of 1%. The pure NaCl solution of the same concentration was used as a control. Nine food sensory professional testers (5 men and 4 women) were called to measure the saltiness of the samples. Before the test, mouthwash was used to clean the mouth to remove the odor, and then the saltiness of the samples was evaluated. The mouthwash was re-rinsed between each sample test to remove the taste of the previous sample. Pure NaCl solution was scored as 1 point, 1-3 points were given for saltiness higher than the control group, and -1--3 points were given for saltiness lower than the control group.
[0020] The quaternized chitosan reacts with the amino and carboxyl groups in succinic acid to form a cross-linked network. During spray drying, the cross-linked network wraps the NaCl in the solution through the spray drying port to form a hollow salt. The higher the degree of cross-linking, the higher the salt embedding amount. Therefore, we measured the degree of cross-linking of the hollow salt samples obtained after ultrasonic and water bath treatment. The results are as follows Figure 1 As shown in Figure A, compared with water bath treatment, ultrasonic treatment can improve the cross-linking degree between quaternized chitosan and succinic acid, among which the hollow salt prepared by ultrasonic 200W, 400W, and 500W treatment has the highest cross-linking degree. Figure 1 B shows the Na embedded in the hollow salt. + The content detection results showed that compared with the water bath treatment, the ultrasonic 500W treatment could increase the embedding amount of NaCl in the hollow structure. This may be because the ultrasonic 500W sample had a higher degree of cross-linking, forming a dense network structure that could firmly lock the NaCl in the hollow structure.
[0021] Example 3: Study on the infrared spectrum, crystal structure and thermodynamic stability of the hollow salt prepared in Example 1.
[0022] FTIR infrared spectrometer was used to analyze the chemical bonds and chemical forces in the hollow salt. Specifically, the hollow salt and KBr were mixed in a ratio of 1:100 (g / g) and pressed into tablets. -1 The chemical bond composition information of the hollow salt was obtained within the scanning range. The crystal state of the hollow salt was studied using an X-ray diffractometer. 0.1 g of the sample was placed in the instrument, and then the X-ray diffraction pattern of the sample was measured in the diffraction angle (2θ) range from 5° to 90° using 40 kV and 30 mA Cu kα radiation. The thermal properties of the hollow salt sample and the changes in its internal structure were evaluated using a differential scanning calorimeter. 3 mg of the hollow salt sample was placed in an aluminum tray and sealed. The scan was performed in the temperature range of 25-250°C, with a heating rate of 20°C / min.
[0023] like Figure 1 As shown in C, water bath and ultrasonic treatment can cause covalent cross-linking between quaternary ammonium chitosan and succinic acid. -1The formation of CN bonds at 3416 cm-1 and the ultrasonic treatment enhanced the strength of the CN bonds, which indicated that the ultrasonic treatment promoted the cross-linking of quaternized chitosan and succinic acid. On the other hand, the ultrasonic treatment destroyed the hydrogen bonds of the hollow salt, causing the OH bonds to shift from 3416 cm-1 to 3416 cm-1. -1 Moved to 3446 cm -1 ; The destruction of hydrogen bonds also makes the -1 The CH bond stretching vibration intensity at 1668 cm -1 There is an absorption peak at 1564 cm, which corresponds to the C=O bond, but there is no such bond in other samples. This may be because ultrasonic treatment may change the morphology or crystallinity of the sample, affect the interaction between molecules, and cause the carbonyl vibration to no longer show an obvious absorption peak. -1 There is an absorption peak at 1437 cm, which corresponds to the C=O bond, and the ultrasonic treatment enhances the peak absorption intensity. This may indicate that the intermolecular or intramolecular hydrogen bond interaction in the sample is weakened, making the C=O bond in a more uniform environment, resulting in a more concentrated vibration frequency of the absorption peak and an increase in intensity. -1 It corresponds to the bending vibration of the CH bond, and ultrasonic treatment increases the peak intensity and narrows the peak shape. This may be because the molecular arrangement becomes more ordered and the environment of the CH bond will be more consistent, which can lead to the narrowing of the absorption peak.
[0024] like Figure 1 As shown in D, the quaternized chitosan raw material has only one diffraction peak at 20.3°, which belongs to the characteristic structure peak of part of the crystal of chitosan. After the cross-linking reaction between the quaternized chitosan and succinic acid, the peak disappears, indicating that the reaction between the quaternized chitosan and succinic acid destroys this part of the crystal structure and transforms it into an amorphous structure. The diffraction peaks at 27.4°, 31.7°, 45.5°, 56.5°, 66.2°, 75.3° and 84° correspond to the characteristic diffraction peaks of the face-centered cubic crystal structure of NaCl, which are the 111 crystal plane, 200 crystal plane, 220 crystal plane, 222 crystal plane, 400 crystal plane, 420 crystal plane and 422 crystal plane of NaCl, respectively, which indicates that the hollow salt contains NaCl. Secondly, the diffraction peak intensities of the 500W group at 31.7° and 45.4° were higher than those of the other groups, indicating that this group had a higher degree of crystallinity and a higher content of embedded sodium chloride, which was consistent with the results of the cross-linking degree determination and the sodium chloride determination.
[0025] like Figure 1As shown in Figure E, compared with water bath heating without salt, the dissolution temperature of the hollow salt is lowered after embedding sodium chloride, which may be because sodium chloride (NaCl) dissociates into sodium ions (Na⁺) and chloride ions (Cl⁻) in quaternized chitosan. These ions interact with the quaternary ammonium cations in the quaternized chitosan molecules, weakening the electrostatic attraction between the quaternary ammonium salt molecules. This effect reduces the binding force between molecules, causing the overall stability of the system to decrease, resulting in a lower melting point. The addition of sodium chloride may also destroy the hydrogen bonds between molecules: the hydrogen bonds in the quaternized chitosan may be destroyed or weakened in the presence of NaCl. Na⁺ and Cl⁻ ions can interact with polar groups (such as hydroxyl and amino groups) in the chitosan molecules, destroying the hydrogen bond network between molecules, thereby lowering the melting point, which can be presumably proven from the infrared spectroscopy results. The dissolution temperature of the hollow salt obtained after ultrasonic pretreatment is lower than that of the sample heated in a water bath. This may be because ultrasonic treatment can make the sodium chloride particles more evenly dispersed in the quaternary ammonium chitosan matrix. This uniform distribution can lead to more interface areas. The interface effect may reduce the thermal stability of the material, thereby causing the melting point to drop. It may also be because ultrasonic treatment can cause partial breakage or degradation of the quaternary ammonium chitosan molecular chain, resulting in a decrease in molecular weight. This decrease in molecular weight usually leads to a decrease in the melting point of the material, because the molecular chain becomes shorter and has a higher degree of freedom, which reduces the energy required for melting. On the other hand, a lower melting point temperature can make the hollow salt dissolve and disperse quickly in the mouth, which is conducive to the diffusion of sodium chloride. However, too low a melting point temperature will cause the hollow salt to be unstable in storage. Therefore, in summary, the hollow salt obtained under 100W, 200W, and 500W ultrasonic treatment conditions has a better effect.
[0026] Example 4: Determination of rheological properties of the hollow salt solution prepared in Example 1.
[0027] The hollow salt powder was dissolved in water to prepare a solution with a mass concentration of 1%. The solution was tested using a rheometer. The sample was placed on parallel plates (diameter 40 mm; gap 1 mm). The apparent viscosity of the hollow salt solution was measured at 25 °C in the range of 0.1 to 100 s -1 Silicone oil was applied to the edges of the parallel plates to prevent water evaporation.
[0028] like Figure 1Figure F shows the viscosity change trend of the hollow salt solution after it is dissolved in water. As the shear force increases, the viscosity of the sample gradually decreases, showing a shear-thinning behavior, which is a typical behavior of non-Newtonian fluids. The reason for this phenomenon is attributed to the breaking of particle / molecular bonds caused by shear or the non-destructive arrangement of the spatial structure and flow direction of the sample. At high shear rates, the sample particles change from an amorphous state to an ordered state, which reduces the viscosity. The chitosan quaternary ammonium salt raw material has a high viscosity, and after cross-linking with succinic acid and spray drying, the viscosity decreases. Excessive viscosity will cause uneven distribution of the hollow salt after dissolution, inhibiting the diffusion of the salt taste. The viscosity of the 100W ultrasonic treatment is higher than that of other groups. This may be because the sample particle size obtained by 100W treatment is larger, resulting in stronger interactions between particles in the solution and increased viscosity. At higher power, ultrasound may cause particle depolymerization or particle size reduction, reducing the interaction between particles and reducing viscosity.
[0029] Example 5. Electronic tongue measurement of the taste of the hollow salt prepared in Example 1.
[0030] Weigh 0.2 g of hollow salt powder and dissolve it in 19.8 mL of deionized water to prepare a 1% concentration solution. Then put the electronic tongue taste sensor into the solution for taste detection, and use the same concentration of quaternary ammonium chitosan solution and pure NaCl solution as controls.
[0031] Figure 2 is the electronic tongue evaluation result of hollow salt, where Figure 2 A is the result of the saltiness test of the hollow salt, Blank is the 1% NaCl solution as the control group. Compared with the control group, the saltiness of the hollow salt obtained after water bath heating and ultrasonic 100W and 300W treatments was slightly reduced, while the saltiness of the hollow salt treated with ultrasonic 200W and 400W was the same as the control group. The saltiness of the hollow salt treated with ultrasonic 500W increased significantly, which is consistent with the sensory evaluation results, indicating that the saltiness of the hollow salt can be increased after ultrasonic treatment. The reason for the increase in saltiness may be that the hollow salt obtained by ultrasonic 500W treatment has a small particle size, which can contact the tongue more fully, and the salt diffusion speed is fast. Figure 2 As shown in Figure B, the richness of the hollow salt after 300W, 400W, and 500W ultrasonic treatment decreased, probably because the salty taste, as the main taste, masked other tastes, resulting in a decrease in the richness of the taste. Figure 2 As shown in Figure C, since the hollow salt contains succinic acid, some uncross-linked succinic acid will diffuse out, resulting in an increase in acidity. Figure 2 As shown in Figure D, the umami intensity of the hollow salt after water bath heating and ultrasonic treatment was lower than that of the hollow salt after water bath heating without umami, which may be because the presence of salt interferes with the umami perception. Figure 2As shown in Figure E, the sensory evaluation results show that compared with the normal 1% NaCl salt solution, ultrasonic 200W and 500W treatment can significantly increase the saltiness of the hollow salt, which is related to its high degree of cross-linking and NaCl embedding amount, and secondly to its small particle size and uniform distribution, which can be proved by the subsequent scanning electron microscopy results and particle size analysis results. From the sensory evaluation results, it can be analyzed that the saltiness of pure NaCl can be achieved by using only 45.36%-53.71% of the weight of pure NaCl in hollow salt.
[0032] Example 6: Effect of ultrasonic treatment on particle size distribution and microstructure of hollow salt.
[0033] The particle size and Zeta potential of the hollow salt were determined by a Zetasizer analyzer. The hollow salt prepared in Example 1 was dissolved in water to prepare a 0.1 mg / mL solution, and then ultrasonically treated at 300W for 5 min to make the sample evenly distributed before testing. The microstructure of the hollow salt was observed using a scanning electron microscope at 15 kV and 1500× magnification.
[0034] Table 1 The results of the average particle size and potential of hollow salt obtained by different treatment methods
[0035] like Figure 3 As shown in A, the particle size of the quaternized chitosan raw material is relatively large, 94.96.64 μm, and the surface has abundant amino groups, which makes the raw material surface carry more positive charges, and the potential shows a higher positive value. After it is cross-linked with succinic acid and then spray-dried, the free amino groups on the surface of the quaternized chitosan react with the carboxyl groups of succinic acid, so the potential of the resulting hollow salt is significantly lower than that of the raw material. The hollow salt prepared by ultrasonic 200W treatment has the lowest potential, which is related to its highest degree of cross-linking. The higher the degree of cross-linking, the more stable the network structure it forms, and the more stable and effective it will be in encapsulating NaCl during spray drying. In addition, the number of free amino groups with positive charges is reduced, which reduces the potential. As Figure 3 Middle B, Figure 3 As shown in Figure C, the particle size of the group without salt coating in the water bath decreased to 7.61 μm, while the particle size after salt coating increased to 10.39 μm. This may be because NaCl was filled into the center of the sphere, which increased the particle size. In addition, the hollow salt particle size obtained by water bath treatment was uneven, and some samples were over 100 μm. This may be because the matrix material will spontaneously agglomerate together to form large particles due to thermodynamics during the water bath heating process. Figure 3 As shown in D, 100W ultrasonic treatment has little effect on the hollow salt particle size, and the particle size is 10.13 μm. Figure 3 Middle E, Figure 3 Medium F, Figure 3 Medium G, Figure 3 As shown in Figure H, the 200-500W treatment further reduced the particle size. The hollow salt prepared by 200W and 500W treatments had the smallest particle sizes, which were 7.63 μm and 7.27 μm, respectively. The smaller particle size was conducive to the rapid diffusion of the hollow salt. Although the hollow salt particle size treated with 300W was also small, the particle size in the 300W treatment group exceeded 100 μm, which may be because ultrasound affected the aggregation and distribution of the hollow salt. The reasons why ultrasound changed the particle size distribution of the hollow salt may be as follows: First, ultrasonic treatment will produce a cavitation effect. The cavitation effect produced by ultrasound will cause the formation and rapid collapse of bubbles in the liquid. The released local high temperature and high pressure environment can break up the particle clusters, making their particle size smaller and more uniform. Secondly, the micro-mixing effect exerted by ultrasonic treatment. The mechanical vibration of ultrasound will cause violent mixing in the liquid and promote the uniform dispersion of the material. This uniform stirring and dispersion effect can prevent excessive aggregation of particles and form a more consistent particle size distribution. Furthermore, ultrasonic treatment also produces a shear effect: the high shear force generated by ultrasound helps to break up large particles or agglomerates, making the particles gradually finer, thereby improving the particle size distribution.
[0036] Figure 4 Scanning electron microscopy results of hollow salts of different groups, such as Figure 4 A in the middle shows the microscopic morphology of the hollow salt prepared by water bath heating treatment and spray drying. It can be seen that its size is large, the size distribution is uneven, and there are many broken hollow salts. Figure 4 Middle B, Figure 4 Middle C, Figure 4 Middle D, Figure 4 Middle E, Figure 4 Middle F is the microscopic morphology of hollow salt obtained by spray drying after ultrasonic treatment at 100W-500W. The particle size of hollow salt after ultrasonic treatment is smaller than that after water bath heating treatment, which is consistent with the particle size analysis results. The size of hollow salt after 100W ultrasonic treatment is larger than that of other ultrasonic treatment groups, and the surface is relatively dry and not smooth. The particle size of hollow salt in the 300W treatment group showed a typical state of different sizes, and some particles were larger, which is consistent with the results of particle size analysis because some individual larger particles were captured. The size distribution of hollow salt in the three groups of samples treated with 200W, 400W, and 500W is more uniform and smaller. The smaller size distribution can be conducive to the dissolution and release of hollow salt, allowing people to quickly perceive the salty taste, thereby reducing salt intake.
[0037] Example 7. Effect of hollow salt pickling prepared in Example 1 on air-dried duck meat.
[0038] 1. Effect of hollow salt pickling on the pH of air-dried duck meat: The quaternized chitosan-succinic acid hollow salt powder embedded with NaCl prepared in Example 1 was evenly applied to the duck meat at 6wt%, and vacuum pickled for 24 h, and then the meat samples were taken out and air-dried for 3 days at 16°C and 65% humidity. 2 g of air-dried duck meat was added to 18 mL of deionized water, homogenized twice at 8000 r / min, each time for 30 seconds, and then the pH value of each group of duck meat samples was measured with a pH meter, and each group of samples was measured three times.
[0039] like Figure 5 Figure A shows the effect of curing with pure NaCl and curing with the same amount of different groups of hollow salt on the pH of air-dried duck. The results show that curing with hollow salt has no significant effect on the pH of air-dried duck compared with curing with NaCl alone. pH can reflect the freshness of meat. The pH of fresh meat is 5.8-6.2. Meat contains more microorganisms. Under the decomposition and metabolism of these microorganisms, they consume the protein and sugar substances in the meat to produce acidic substances to reduce the pH. If the pH drops too much, it will have an adverse effect on the quality of meat products. NaCl has the effect of inhibiting the growth of corrupt microorganisms, and curing with hollow salt does not increase the degree of corruption of meat products, indicating that it has achieved the effect of reducing salt and preventing corruption.
[0040] 2. Effect of hollow salting on TVB-N of air-dried duck meat: For the determination of volatile basic nitrogen (TVB-N), 4 g of air-dried duck meat was mixed with 26 mL of pure water and homogenized at 10000 rpm / min for 1 min to fully break the meat sample. Then centrifuge at 8000 rpm for 10 min, take 10 mL of the supernatant and mix it with 5 mL of magnesium oxide solution (10 g / L), then transfer it to the digestion tube, use the fully automatic Kjeldahl nitrogen analyzer to distill for 5 min, collect the distillate, add 2-3 drops of mixed indicator (methyl red-methylene blue, 0.05 mol / L) to it, and then titrate the distillate with 0.01 mol / L hydrochloric acid to stop the titration when its color changes from colorless to pink.
[0041] like Figure 5 B shows the effect of curing with pure NaCl and curing with the same amount of different groups of hollow salt on the TVB-N of air-dried duck. Compared with curing with NaCl alone, curing with hollow salt can reduce the TVB-N value of air-dried duck, among which curing with 100W, 300W, 400W, and 500W hollow salt has a better effect on protein corruption. This may be because hollow salt has a special hollow structure and has a larger specific surface area than ordinary table salt, which allows hollow salt to penetrate into the meat product more effectively during the curing process, thereby improving the curing efficiency, and the uniform distribution of NaCl reduces the degree of protein corruption.
[0042] 3. Effect of hollow salting on TBARS of air-dried duck meat: For the determination of fat oxidation degree (TBARS), in short, 4 g of air-dried duck meat sample was accurately weighed and 36 mL of 10% (v / v) trichloroacetic acid was added. Homogenize at 8000 rpm / min for 1 min, then centrifuge at 8000 rpm for 10 min. Take 2 mL of supernatant and mix with 2 mL of 0.02 mol / L thiobarbituric acid solution, heat at 90℃ for 40 min, then cool to room temperature, take 200 μL of supernatant and measure the absorbance value at 532 nm.
[0043] like Figure 5 Figure C shows the effect of curing with pure NaCl and curing with the same amount of different groups of hollow salt on TBARS of air-dried duck. The results show that curing with hollow salt can reduce the degree of fat oxidation in air-dried duck meat, among which the 200W-500W hollow salt group has a better curing effect. The structure of hollow salt may help reduce the contact area between oxidants such as oxygen and fat in meat products, thereby reducing the chance of oxidation reaction; metal ions can promote the formation of free radicals in meat products, for example, iron ions and copper ions can accelerate fat oxidation, and hollow salt may slow down the fat oxidation process by reducing the catalytic effect of metal ions such as iron and copper.
[0044] 4. Effect of hollow salt curing on the sensory quality of air-dried duck meat: 10 professionally trained personnel were recruited to conduct sensory evaluation of air-dried duck meat. The samples were evaluated from the perspectives of color, texture, flavor, taste, and overall acceptability. The score was 10 points. The better the color, texture, flavor, and taste, the higher the score. Each reviewer scored independently without interfering with each other. They rinsed their mouths between tasting each group of samples to prevent cross-contamination of samples from affecting the evaluation results. Table 2 shows the effects of curing with pure NaCl and curing with the same amount of hollow salt in different groups on the sensory quality of air-dried duck.
[0045] Table 2 Effects of hollow salt obtained by different treatments on the sensory quality of air-dried duck
[0046] As shown in Table 2, the use of hollow salt can improve the sensory quality of dry-cured meat products, especially the hollow salt obtained after 400W and 500W ultrasonic pretreatment and spray drying has a higher degree of improvement in sensory quality. This is related to its smaller particle size, which can improve the perception of saltiness, penetrate more fully into the meat tissue, and improve the flavor uniformity and overall flavor balance. The improvement in color is related to the hollow salt reducing the degree of lipid oxidation. The color will be more red when the degree of oxidation is low. The main reason for the improvement in texture is that the polysaccharides contained in the hollow salt penetrate into the meat tissue to increase the water retention of the meat, making the texture of the air-dried duck meat softer.
[0047] The above description is not intended to limit the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by a person skilled in the art within the spirit and scope of the present invention shall also fall within the protection scope of the present invention.
Claims
1. A method for preparing quaternary ammonium chitosan-succinic acid hollow salt, characterized in that The method comprises the following steps: mixing quaternary ammonium chitosan, succinic acid, NaCl and deionized water in a mass ratio of 1:2.36:15:81.64, stirring and uniformly dissolving, treating under ultrasonic conditions of 100-500W for 20-40 minutes, spray drying after the ultrasonic treatment, and obtaining quaternary ammonium chitosan-succinic acid hollow salt embedded with NaCl.
2. The method for preparing a quaternary ammonium chitosan-succinic acid hollow salt according to claim 1, characterized in that: During the spray drying process, the inlet air temperature of the spray dryer was set to 140° C., the fan frequency was set to 10 rpm, and the solution injection speed was set to 20 mL / min.
3. The method for preparing a quaternary ammonium chitosan-succinic acid hollow salt according to claim 1, characterized in that: The water bath temperature was set to 60°C during ultrasonic treatment.
4. The method for preparing a quaternary ammonium chitosan-succinic acid hollow salt according to claim 1, characterized in that: The ultrasonic power is 400W or 500W.
5. Use of the quaternary ammonium chitosan-succinic acid hollow salt obtained by the preparation method according to any one of claims 1 to 4 in air-dried duck meat.
6. The use of the quaternary ammonium chitosan-succinic acid hollow salt obtained by the preparation method according to claim 5 in air-dried duck meat, characterized in that: The added mass percentage of hollow salt used for pickling duck meat is 6%, the air-drying time is 3 days, and the air-drying temperature is 16°C.
Citation Information
Patent Citations
Curdlan-quaternized chitosan conjugate nanoparticle, and preparation method and application thereof
CN112451659A
NaCl microsphere with hollow structure and preparation method thereof
CN114568681A
Preparation method and application of salt particles with salt reducing effect
CN115299584A
Making method of fermented dry-cured duck with low nitrite residue
CN118436054A
Crosslinker-free preparations
DE19932075A1
